(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Gold nanoparticles (Au NPs) are effective agents for early diagnostic and treatment of a variety of diseases, including cancer. However, initial components in the synthesis like surfactants, which are commonly used to stabilize nanoparticles, can produce toxic effects on living organisms. Thus, finding ways to reduce the toxicity of nanoscale preparations is an actual problem. In this regard the essential aminoacid tryptophan (Trp) is a promising reagent for the synthesis of Au NPs that can serve as a reducer of Au(ІІІ) ions and particle stabilizer. In this work, in order to increase the biocompatibility of the nanoscale system, the synthesis of gold nanoparticles was performed in the presence of Trp. The reaction between HAuCl4 and Trp proceeded in aqueous medium with neutral pH at different temperatures. Spectral characteristics of products formed in Au/Trp systems and were studied. In the absorption spectra the main band of Trp at 280 nm was shifted to 250 nm during the reaction; for all studied systems upon excitation of fluorescence with the wavelength of λex = 340 nm the maximum of the emission bands were observed at λem = 450 nm, while for initial tryptophan (λex = 280 nm) it was located at λex = 375nm. Mass spectra of Trp solution in positive mode contained the signal at 131 Da, that was characteristic for ionized indole moiety of amino acid. For supernatants of studied Au/Trp systems in positive mode signals of ionized fragments with masses of 118, 146 and 174 Da were observed. Based on the data it was revealed that amino acid oxidation proceeded through the formation of kynurenine or through the "kynurenine pathway", that corresponds to the metabolic conversion of amino acid in human organism and proves the biocompatibility of formed products.